Correlation between Seminal Fructosamine and Glycosylation Gap and Some Sex Hormones in the Young Infertile Male in Mosul City - Ahmed AlKataan, Muhammad Abdulgafoor; Junaid Salim, Moamin (Iraqi Journal of Pharmaceutical Sciences, 2022)
Infertility represents a growing health problem in Mosul city and worldwide. Infertility defined as a failure to induce pregnancy after unprotected sexual intercourse for more than 12 months. Infertility in male is a multifactorial complex pathology that leads to different types of problems. This work try to explore the correlation between glycosylation gap and seminal fructosamine and another parameter in the young male patient in Mosul city. The study included 50 subjects with age range 19-29 year with BMI 18-26. The infertility group include 25 patients newly diagnosed with infertility before starting any treatment; have no infection and no structural abnormality. The control group included 25 healthy subjects. HbA1c, fructosamine, Serum and seminal Testosterone, estradiol and Testosterone/ estradiol. Plasma trace element as K, Mg and Zn also measured. There was a significant elevation in the glycosylation profile in the infertile male in compare to control (p<0.05). There was a significant elevation in glycosylation gap in the infertile group (p<0.01). Testosterone and Testosterone/ Estradiol ratio significantly reduced in the infertile group in comparison to control group (p< 0.0004 and 0.0002 respectively). Serum and Seminal plasma Testosterone/ Estradiol ratio showed no significant changes between the two groups (p>0.05). In conclusion, there was a significant positive correlation seminal plasma fructosamine and glycosylation gap in infertile male group.